Enantio‐ and Diastereoselective Suzuki–Miyaura Coupling with Racemic Bicycles - Goetzke, F. Wieland (Angew Chem Int Ed Engl, 2019)
Herein, we describe a rhodium‐catalyzed enantio‐ and diastereoselective Suzuki–Miyaura cross‐coupling between racemic fused bicyclic allylic chlorides and boronic acids. The highly stereoselective transformation allows for the coupling of aryl, heteroaryl, and alkenyl boronic acids and gives access to functionalized bicyclic cyclopentenes, which can be converted into other five‐membered‐ring scaffolds with up to five contiguous stereocenters. Preliminary mechanistic studies suggest that these reactions occur with overall retention of the relative stereochemistry and are enantioconvergent for pseudo‐symmetric allylic chloride starting materials. In addition, a bicyclic allylic chloride starting material without pseudo‐symmetry undergoes a highly enantioselective regiodivergent reaction.